Musing on the Language of Literature - Neupane, Nabaraj (Janapriya Journal of Interdisciplinary Studies, 2020)
Literature conveys human ideas, thoughts, emotions, feelings and experiences artistically. The use of distinctive grammatical, semantic, and stylistic conventions make the language of literature a field-based register. Based on these presumptions, this article aims to elucidate the deviant features that are prevalent in the literary texts. To obtain the objective, I have employed qualitative content analysis that calls for interpreting the extracts from the authentic literary discourses. The main findings are related to the five-fold features such as grammatical, semantic/lexical, graphological, prosodic, and ornamental, which create markedness of the literary register. These findings reveal that the litterateurs use figures of speech to beautify the presentation of feelings and ideas. This implies that the readers, the writers, and the material producers (like curriculum designers and textbook writers) should be aware of the marked features of the literary texts.